Effectiveness Of Mix Police (Fiscal And Monetary Police) In Reducing Unemployment In 5 Southeast Asia Countries (Indonesia, Malaysia, Thailand, Singapore And Philipnes) - Novita Iswahyuni; Bachtiar Efendi; Rusiadi (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study aims to analyze the contribution of the effectiveness of the mix police (fiscal and monetary police) in reducing unemployment in 5 Southeast Asian countries (Indonesia, Malaysia, Thailand, Singapore and the Philippines). This study uses secondary data or time series, namely from the first quarter of 2001 to the fourth quarter of 2018. The data analysis model in this study is the Vector Autoregression (VAR) model and the ARDL Panel then sharpened by analysis of Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD). The results of the Vector Autoregression analysis show that the past variable (t-1) contributes to the present variable both on itself and on other variables. From the estimation results, it turns out that there is a reciprocal relationship between one variable and the other variables that contribute to each other.